Financing decision, ownership type and financial performance of listed non-financial companies in Ghana - Francis Aboagye-Otchere; Prince Yeboah Boateng (Cogent Business & Management, 2023)
The study aims to investigate the nexus between financing decision, ownership type and financial performance of listed non-financial companies in Ghana. Data were selected from 22 listed non-financial companies on the Ghana Stock Exchange from the years 2010 to 2021. A non-parametric estimation technique-robust OLS (Driscoll-Kraay) was employed to test the variables of interest. Findings indicate that long-term debt funding directly affects ROA, ROE and TQ negatively. Again, total debt funding posits a positive link with ROE and TQ. Moreover, the direct relationship between ownership type, financing decision and accounting-based performance measure (ROE) was insignificant but significant with market-based performance measure (TQ). Subsequently, the interaction role propelled ownership (foreign and state) to be significant on the relation between financing decision and financial performance. Largely, foreign-owned companies play a strong positive role on the link between financing decision and financial performance. Further, state ownership negatively affects the association between financing decision and financial performance. The study contributes to knowledge by considering the multiplier effect of ownership type on the relationship between financing decision and financial performance in Ghana. For policy implication, regulators specifically of state interest entities should formulate balanced frameworks for welfare seeking in public service delivery and performance for sustainability.
Keywords: 650; financial performance; agency theory; Ghana; Financing decision; listed non-financial companies; ownership type